PENERAPAN GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN MELALUI PROFITABILITAS (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Sholichah, Elva Kumalasari; Puspawati, Dewita (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research aims to examine the Implementation of Green Accounting Corporate Social Responsibility on Company Profitability Scores in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research is quantitative with an associative approach. Quantitative quantitative research is considered scientific because it follows systematic, concrete, objective, measurable and rational scientific principles. The data used in this research is secondary data using library data collection techniques obtained from the official website of the Indonesian Stock Exchange. All data obtained was analyzed using the SPSS analysis tool. The results of this research show that there is an influence of GA on company value at a significance level of 0.000. 1) The influence of CSR on company value at the 0.000 significance level. 2) GA affects company profitability at a significance level of 0.029. 3) CSR affects company profitability at a significance level of 0.072. 4) Profitability has a significant influence on company value at the 0.000 significance level. 5) The existence of profitability mediates the influence of GA on company value at a significance level of Z 2.322. 6) Profitability does not mediate the effect of CSR on company value at a significance level of Z 1.743. Keywords : Green Accounting, Corporate Social Responsibility, Company Value, Profitability